Natural polyphenols enhanced the Cu(II)/peroxymonosulfate (PMS) oxidation: The contribution of Cu(III) and HO. (1st November 2020) - Wang, Yu; Wu, Yang; Yu, Yafei; Pan, Tao; Li, Dantong; Lambropoulou, Dimitra; Yang, Xin
Highlights: Gallic acid (GA)/Cu(II)/PMS effectively degraded TBBPA at pH 4.3 − 9.0. Cu(III) was the dominant oxidant responsible for TBBPA degradation. GA acted as electron donor to accelerate Cu redox cycling for PMS activation. TBBPA degraded via electron abstraction, debromination and ring-opening pathways. Cu(II) and NOM present in water can activate PMS to degrade TBBPA effectively. Abstract: Copper ion (Cu(II)) in water or wastewater has been reported to trigger peroxymonosulfate (PMS) oxidation of organic contaminants (OCs). However, this process can only work in alkaline condition, which limits its potential application. In this study, we found that the introduction of natural polyphenols in the Cu(II)/PMS process can significantly promote the degradation of tetrabromobisphenol A (TBBPA), one of the most widely used brominated flame retardants, in the pH range of 4.3−9.0. With gallic acid (GA) as a representative natural polyphenol, the degradation of TBBPA by GA/Cu(II)/PMS process reached 84.6% in 10 min at initial pH of 4.3 (without pH adjustment), which was 2.2 times higher than that by Cu(II)/PMS process. Multiple reactive oxidants, including Cu(III), hydroxyl radical (HO ) and singlet oxygen, were generated in this process among which Cu(III) and HO contributed to TBBPA degradation with Cu(III) playing the dominant role. GA accelerated the reduction of Cu(II) to Cu(I) due to the strong chelation and electron-donating capacity of ortho-hydroxyl groups in GA, and then Cu(I) was quickly oxidized by PMS to Cu(III) which can be further acid-catalyzed to produce HO . TBBPA transformation mainly proceeded through electron abstraction, oxidative debromination and ring-opening reaction pathways. The feasibility of in-situ utilizing natural organic matter (NOM, enriched with polyphenol moieties) to accelerate the degradation of TBBPA by Cu(II)/PMS process in surface water and wastewater was confirmed. The findings of this study indicate that the coupling of NOM and Cu(II), which are present in contaminated water or wastewater, can potentially improve PMS oxidation of OCs in a wide range of pH. Graphical abstract: Image, graphical abstract